(x+3)^2 = 13 ---------- original

when we take under root we get two equations

(x+3) = +√13 ----(equation 1) (x+3) = -√13 ------- (equation 2)

equation 1 goes to form equation 2 goes to form

x=+√13 - 3 x=-√13 -3]]>

I still don't get it. I learned that √(x) or x^(1/2) is the principal square root of x.

Who says you should only use the principal root in this case. That would only get one root, a quadratic has 2 roots. See post #2

]]>How to think when getting from this step [(x+3)^2 = 13] to [(x+3) = ±√13]?

I mean, why the last step is written like that? Why not (±(x+3)=√13)?

What makes both (±(x+3)=±√13) and (∓(x+3)=±√13) valid?

1) x+3=√13 => x=√(13)-3

2) -(x+3)=-√13 => x=√(13)-3

3) x+3=-13 => x=-√(13)-3

4) -(x+3)=√13 => x=-√(13)-3

It is usually written like this but you are essentially correct.

(x+3)^2 = 13

(x+3) = ±√13

]]>Say, (x^2)+6x-4=0, then by completing the square I get:

(x^2)+6x-4= 0

(x^2)+6x = 4

(x^2)+6x+9= 4+9

(x+3)^2= 13

Now, why isn't sqrt((x+3)^2) also equal to -(x+3)=-x-3?

Many small questions have been popping up in my head. This is leading me to a confused state. I used to do well and understand algebra, but I don't what happened, things started becoming confusing and unclear.

]]>